Assessing the impact of off-farm employment on land efficiency in different patterns: Field evidence from post-reform China - Zhao, Sudan; Pei, Siyi; Jiang, Yongmu; Wu, Xianqiang (Frontiers in Environmental Science, 2022)
The Three Rights Separation Reform (TRSR) has laid a concrete foundation institutionally to guide the well-ordered transfer of farmland and promoting the development of urbanization. With the new economics of labour migration (hereinafter referred to as the NELM) theory as the analytic basis, this empirical research investigates the potential ramifications of off-farm employment on land efficiency with household-based survey data from four provinces in China after TRSR. Unlike existing studies, we delve into how the effects are manifested differently among the types of off-farm employment by adopting an ordinary least squares (OLS) model and a two-stage least squares (2SLS) estimator. It provides evidence that migration positively affect land efficiency significantly, whereas a negative impact of local off-farm employment on land efficiency is observed, which distinct this study from previous findings. From the perspective of policy-making, land administrators should realize that off-farm employment differentiation is an important factor affecting land efficiency, and therefore needs to be fully considered in policy-making. Meanwhile, the establishment of local labor markets and favorable policies that stimulate productive technologies are needed.